2017
DOI: 10.1002/wnan.1478
|View full text |Cite
|
Sign up to set email alerts
|

Oral nucleic acid therapy using multicompartmental delivery systems

Abstract: Nucleic acid-based therapeutics has the potential for treating numerous diseases by correcting abnormal expression of specific genes. Lack of safe and efficacious delivery strategies poses a major obstacle limiting clinical advancement of nucleic acid therapeutics. Oral route of drug administration has greater delivery challenges, because the administered genes or oligonucleotides have to bypass degrading environment of the gastrointestinal (GI) tract in addition to overcoming other cellular barriers preventin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 151 publications
0
14
0
Order By: Relevance
“…Interestingly, the multi functional nanodelivery system containing nucleic acid showed effective antiinflammatory effects through downregulating or silencing the gene expression associated with inflammation in the IBD mice. [94] Aside from above effects, nanomaterials can also improve the therapeutic effect of oral vaccines for intes tinal autoimmune diseases as immune adjuvants. Moreover, NMs with different modification can also resist the invasion of Salmonella enteritis and prevent anaphylactic shock through modulating immune responses through enhancing Th1 effect, the release of Treg cytokines, and immune memory.…”
Section: Effects Of Nanomaterials On Intestinal Immunity and Their Pomentioning
confidence: 99%
“…Interestingly, the multi functional nanodelivery system containing nucleic acid showed effective antiinflammatory effects through downregulating or silencing the gene expression associated with inflammation in the IBD mice. [94] Aside from above effects, nanomaterials can also improve the therapeutic effect of oral vaccines for intes tinal autoimmune diseases as immune adjuvants. Moreover, NMs with different modification can also resist the invasion of Salmonella enteritis and prevent anaphylactic shock through modulating immune responses through enhancing Th1 effect, the release of Treg cytokines, and immune memory.…”
Section: Effects Of Nanomaterials On Intestinal Immunity and Their Pomentioning
confidence: 99%
“…The multicompartmental systems evaluated in this study, TG2-NiE and TG2-NiMOS, were specifically designed to evade these extra-and intracellular barriers to facilitate oral nucleic acid delivery. 25,26 Prior in vitro evaluations with GNPs showed that GNPs were capable of efficiently encapsulating siRNA, delivering siRNA to the cellular cytoplasm, and enabling functional RISC loading of delivered siRNA. Further, when tested in an in vitro model of CD, the knockdown of IL-15, either specific or an adjunct with TG2, showed significant downregulation in the expression of proinflammatory cytokines-TNF-a and IFN-c. 22 Our current objective was to develop an oral siRNA delivery system that is capable of inhibiting expression of target proteins in the small intestine, aimed at developing a potential treatment for patients with CD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the size of carriers, negative surface charge and hydrophilic surface decoration are also strategies utilized for passive targeting to the inflamed intestinal tissue [ 9 , 10 , 11 ]. The local delivery of OND has been investigated using many kinds of polymeric nanoparticles [ 12 ], lipid nanoparticles [ 13 ], microencapsulated nanogel [ 14 ], thioketal nanoparticles [ 15 ] and nanoparticles-in-microspheres multicompartment systems [ 16 ].…”
Section: Introductionmentioning
confidence: 99%